Research and Scholarly Activity in US Anesthesiology Residencies: A Survey of Program Directors and Residents. (12th April 2012) - Nasr, Viviane G.; Ahmed, Iqbal; Bonney, Iwona; Schumann, Roman
Abstract : Background . Effective 2007, the ACGME required scholarly activity during residency. Although many programs have ongoing research, residents' involvement may be limited. This US anesthesiology residency survey assesses the current scholarly environment, research activity and program support during training. Methods . Following IRB approval, 131 US anesthesiology program directors were invited to participate in a web-based survey. Questions to directors and residents included program structure, research activity, funding and productivity. We categorized residencies threefold based on their size. Results are summarized descriptively. Results . The response rate was 31.3% (n = 41 ) for program directors and 15.3% (n = 185 ) for residents. Residents' responses mirrored those of program directors' regarding the presence of didactic curricula (51% versus 51.9%), research rotations (57% versus 56.2%) and a project requirement (37% versus 40%). Demands of residency (27.0%) and early stage in training (22.2%) were the main obstacles to research cited by trainees. Residents' financial support was available in 94.3% of programs. Medium and large programs had multiple funding sources (NIH, industrial and private). Conclusion . Programs are dedicated to incorporate research into their curriculum. Residents' financial support and mentorship are available, while research time is limited. Systematic improvements are needed to increase trainee research in US anesthesiology residencies.